TEACHING ENGLISH WITH SPEAKING FOR TOURISM MODULE (STM) BASED ON FOLKTALE IN LARIKE VILLAGE - Nusi, Ahmad; Marantika, Meyke; Wuarlela, Mouren (TELL - US JOURNAL, 2022)
English in vocational learning is given more attention to the English culture (source culture) rather than local culture (target culture). Furthermore, the demand of English speaking in tourism is increasing significantly and this leads to design a new of teaching material based on local culture. This study aims to design teaching material based on local culture known as folktale in Larike village, Ambon. Maluku. This study obviously used research and development (R&D) by following the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The first results obviously shown that destination and tourist information got the highest percentage (80%). Tradition was the next rank with percentage (65%) followed by shopping and sightseeing (36%). In addition, the language functions that they need the most is asking for and giving information with percentage (60,8%). Then, it also clearly obtained describing an object in the second rank with percentage (54,1%) and asking for and giving directions with percentage (45,2%). In the development stage, speaking for Tourism Module (STM) based on folktale were eligible based on the experts and students’ validation with average score of holistic Aiken index respectively 0,876 (valid) and 0.795 (valid). The second result of Speaking for Tourism Module (STM) based on folktale on small-scale implementation with scored 81.74% and large-scale trials obtained a score of 85%. In conclusion, based on the value obtained, Speaking for Tourism Module (STM) based on folktale was feasible (very valid) to be implemented to the students in Larike village.